Antiretroviral therapy non-adherence among children living with HIV in Dire Dawa, Eastern Ethiopia: a case-control study - Melkamu Merid Mengesha; Mulugeta Embibel; Tesfaye Gobena; Abayneh Tunje; Degu Jerene; Inger Kristensson Hallström (BMC, 2022)
Abstract Background: In 2018, nearly 90% of the global children living with human immunodeficiency virus (HIV) were in sub-Saharan Africa (SSA). Compared to the adult population, antiretroviral therapy (ART) coverage among children was limited. However, adherence remained a problem among children though they had limited access to ART. This study was conducted to identify the risk factors of non-adherence to ART among children aged 6 to 17 years. Methods: This case-control study was conducted in 2020 using data obtained from clinical record reviews and self-reported data from 272 caregivers of HIV-infected children aged 6-17 years. Cases and controls represented children with poor versus children with good adherence to ART, respectively. Good adherence was defined based on a past 30-day physician adherence evaluation of taking ≥ 95% of the prescribed doses. Binary logistic regression was used to identify factors associated with non-adherence to ART. All statistical tests are defined as statistically significant at P-values < 0.05. Results: Of the 272 children, for whom data were obtained, 78 were cases and 194 were controls; females accounted for 56.3%, 32% attended secondary school, and for 83.1%, the reporting caregivers were biological parents. Non-adherent children had higher odds of association with the following risk factors: a caregiver who is a current substance user (aOR = 2.87, 95% CI: 1.44, 5.71), using AZT-and ABC-based regimen compared to the TDF-regimen (AZT-based, aOR = 4.12, 95% CI: 1.43, 11.86; ABC-based, aOR = 5.58, 95% CI: 1.70, 18.30), and had an increase in viral load from baseline compared to those remained undetectable (remained at or decreased to < 1000, aOR = 4.87, 95% CI: 1.65, 14.33; remained at ≥ 1000, aOR = 9.30, 95% CI: 3.69, 23.46). In contrast, non-adherent children had 66% lower odds of being at early adolescent age compared to 6-9 years old (10-14 years, aOR = 0.34, 95% CI: 0.12, 0.99) and had 70% lower odds of being aware of their HIV status (aOR = 0.30, 95% CI: 0.13, 0.73). Conclusion: Technical support to caregivers to build disclosure self-efficacy, identifying the appropriate regimen for children, counseling on viral load suppression on subsequent visits, and helping caregivers avoid or reduce substance use may help improve the problem of children's non-adherence to ART.